School climate and adaptive characteristics of younger primary school students - Đurišić, Maša; Žunić-Pavlović, Vesna (Specijalna edukacija i rehabilitacija, 2021)
Introduction. It has long been established that school climate can influence the course and outcomes of education, but the findings of previous research are inconsistent as to which elements of school climate are crucial for positive outcomes. This paper provides a more detailed insight into the individual contribution of the dimensions and determinants of school climate for adaptive functioning of students. Objective. The objective of the research was to consider the patterns of the relationship between the quality of school climate and its determinants (program, process and material) and adaptive characteristics of students. Methods. The research was conducted in five primary schools in Belgrade. The Charles F. Kettering, Ltd. – CFK School Climate Profile was used to assess school climate, and the TRF Adaptive Functioning Profile was used to assess adaptive characteristics of students. Both questionnaires were completed by primary school teachers. Results. Positive correlations were found between the quality of school climate, program, process and material determinants, on the one hand and, on the other hand, adaptive characteristics of students. Based on the results of regression analysis, the program determinants of school climate were singled out as the only significant predictor. Conclusion. The results of this research confirm that a good school climate, and especially school programs and practices in the domain of learning and teaching, can contribute to adaptive characteristics of students. Based on the obtained results, the paper describes the implications for future research and practice in this field.